Development of Small Holder Plantation Forests: An Analysis from Policy Process Perspective - Hariadi Kartodihardjo; Bramasto Nugroho; Didik Suhardjito; Ahmad Dermawan (Jurnal Manajemen Hutan Tropika, 2013)
This research was conducted to learn the inhibiting factors for renewal of forest utilization policy, particularly the policy of small holder plantation forests/HTR), by government. To achieve the objective of this research, there were studies on contents of law and regulations, respond of stakeholders toward those law-regulations, and problem of contents and constraints of law and regulations improvement through analysis approach of policy making process. It was found that technical constraints in HTR development were weak provision of forest territory and poor institutional strengthening of the participant community to be ready to receive permit or fund for HTR development.  Such phenomena were due to contents of HTR policy which have more tendencies to answer the problem of absence of bureaucracy and administration procedure which should be determined on the basis of authorities of agencies of central and local government, rather than answering the problem faced by HTR participant community. Policy narrative in the past period in implementing large business policy of natural forest utilization were still dominant, accompanied with weak consideration in making and implementing policy toward forest territory conflict and weak socio-economic and bargaining position of the community, resulting in expensive public service which could not fulfill the community's need.